Learning to Write Experiment Report Text using Project-Based Learning Method - Mulyani Mulyani; Teti Sobari (IKIP Siliwangi, 2023)
The problem in this study was the low result/score of students' skills in writing test report texts. One of the alternatives as a solution to this problem is the author applying a project-based learning method or project based learning (PjBL). The purpose of this study was to determine the increase in students' skills in writing test report texts. after applying the PJBL method. The research procedure uses classroom action research by processing data in a qualitative descriptive manner. The research was started by carrying out pre-action/pre-cycle activities, namely identifying students' skills in writing experimental report texts in class IX B SMPN 8 Cimahi. Based on the results of the prasikus, action research was carried out which consisted of two cycles. Each cycle consists of two meetings. The actions in each cycle are carried out in four stages, namely (1) preparation/planning and action, (2) implementation of actions, (3) observation and evaluation, and (4) reflecting on the actions that have been carried out in learning activities. As for the results of this study, students experienced an increase in learning outcomes in writing experimental report texts, namely as follows: Pre-cycle to cycle 1 experienced an increase. achievement of completeness is 68.42. This shows an increase in students' skills in writing experimental report texts from pre-cycle which completed 9 students increased to 26 students in cycle I. Students' skills in writing experimental report texts by applying PJBL increased by 31.58 from the results in cycle I to cycle II. This proves that the PjBL method can improve the skills of class IX B students in writing trial report texts. All 38 students passed with the highest score of 90 and the lowest score of 79.